2021
DOI: 10.1371/journal.pone.0252504
|View full text |Cite
|
Sign up to set email alerts
|

HeLa TI cell-based assay as a new approach to screen for chemicals able to reactivate the expression of epigenetically silenced genes

Abstract: Chemicals reactivating epigenetically silenced genes target diverse classes of enzymes, including DNMTs, HDACs, HMTs and BET protein family members. They can strongly influence the expression of genes and endogenous retroviral elements with concomitant dsRNA synthesis and massive transcription of LTRs. Chemicals reactivating gene expression may cause both beneficial effects in cancer cells and may be hazardous by promoting carcinogenesis. Among chemicals used in medicine and commerce, only a small fraction has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Kantidze et al demonstrated that CBL0137 possesses chromatin remodeling activity [ 18 ]. This result is in agreement with the ability of CBL0137 to activate epigenetically silenced genes, which was shown in our previous studies on HeLa TI (HeLa Trichostatin-Induced) cells with the epigenetically silenced reporter gene GFP [ 19 , 20 ]. HeLa TI cell treatment with CBL0137 caused the significant activation of GFP expression similar to 5-azacytidine (5-Aza) or Trichostatin A (TSA).…”
Section: Introductionsupporting
confidence: 92%
“…Kantidze et al demonstrated that CBL0137 possesses chromatin remodeling activity [ 18 ]. This result is in agreement with the ability of CBL0137 to activate epigenetically silenced genes, which was shown in our previous studies on HeLa TI (HeLa Trichostatin-Induced) cells with the epigenetically silenced reporter gene GFP [ 19 , 20 ]. HeLa TI cell treatment with CBL0137 caused the significant activation of GFP expression similar to 5-azacytidine (5-Aza) or Trichostatin A (TSA).…”
Section: Introductionsupporting
confidence: 92%
“…We analyzed the ability of XL and NP–XL to reactivate epigenetically repressed genes with HeLa TI cell-based test system, representing HeLa cells harboring the epigenetically silent GFP reporter gene. Previously, we verified the possibility of using this cell population as a model for the detection of epigenetically active xenobiotics [ 64 , 65 ]. Under an epigenetically active compound’s influence, GFP gene expression is reactivated, and GFP-positive (GFP+) cells can be easily detected by flow cytometry.…”
Section: Resultsmentioning
confidence: 87%
“…To determine the epigenetic activity of LCS-1208 and LCS-1269, the HeLa TI test system was used. HeLa TI is a polyclonal population of HeLa cells containing a genome-integrated vector (derived from avian sarcoma retrovirus) carrying epigenetically repressed GFP and capable of detecting inhibitors of histone deacetylases, DNA methyltransferases, bromodomains and some histone methyltransferases [ 41 , 42 ]. The baseline level of GFP-positive cells in the population ranges from 3.5 to 5%.…”
Section: Resultsmentioning
confidence: 99%